Psychology : an introduction - Lahey, Benjamin B. (New York : McGraw-Hill Higher Education, 2012)
'A contemporary take on a time tested classic. Students will master the central concepts of psychology with the new 11th edition of Psychology from Benjamin Lahey. The 11th edition has been thoroughly updated to include the latest research with an emphasis on Chapters 6 (Consciousness), 10 (Development) 14 (Abnormal) and 16 (Social Psychology). Lahey weaves scholarship based on empirical research throughout the text, ensuring an accurate portrait of contemporary psychology. The text's student-friendly writing, clear chapter openers, and fresh applications make the material more relevant to students than ever before, and the proven learning system ensures that all students will grasp the concepts presented in the book. Lahey's hallmark emphasis on diversity and culture remains integrated throughout the text, making this the text for a well rounded introduction to all areas of psychology'--
Includes bibliographical references and index.
Keywords: Psychology -- Textbooks